Multiplex droplet digital PCR for the detection and quantitation of Streptococcus pneumoniae, Mycoplasma pneumoniae, and Haemophilus influenzae - Yaling Cao; Junwen Wang; Yitong Jiang; Ling Xu; Yuan Tian; Zihao Fan; Zhenzhen Pan; Yinkang Mo; Xianru Zhu; Xiangying Zhang; Jing Huang; Feng Ren (Frontiers in Cellular and Infection Microbiology)
BackgroundLower respiratory tract infection is one of the major causes of disease and death worldwide. Streptococcus pneumoniae, Mycoplasma pneumoniae, and Haemophilus influenzae are important pathogens responsible for lower respiratory tract infection. Here, we established a multiplex droplet digital polymerase chain reaction (ddPCR) method for the simultaneous detection of S. pneumoniae, M. pneumoniae and H. influenzae DNA.MethodsSpecific primers and probes were designed for ddPCR. The sensitivity and specificity of the ddPCR assay were evaluated using standard strains, positive samples and 26 common pathogenic bacteria. One hundred and sixty-seven clinical samples were collected and tested via ddPCR, qPCR, bacterial culture and microfluidic chip technology.ResultsThe limits of detection (LoDs) of ddPCR were 2.5, 2.8 and 2.0 copies/μL for S. pneumoniae, M. pneumoniae and H. influenzae, respectively, which were approximately tenfold lower than the LoDs of qPCR. For 167 clinical samples, the positivity rates of ddPCR and microfluidic chip for S. pneumoniae and M. pneumoniae were 27.5% and 22.8%, respectively, which were higher than those of qPCR 25.7% and 21.6%. The positive rate of H. influenzae detection via ddPCR and microfluidic chip method was 29.9%, which was higher than that of qPCR (28.7%). The clinical sensitivity for S. pneumoniae, M. pneumoniae and H. influenzae improved from 97.4%, 94.7% and 95.1% for qPCR to 100% for ddPCR. Moreover, ddPCR showed less inhibition by the inhibitor in respiratory specimens than qPCR.ConclusionThe multiplex ddPCR assay established in this study can accurately detect S. pneumoniae, M. pneumoniae and H. influenzae DNA and can be used as an auxiliary tool for the clinical identification of pathogens and guidance of antibiotic therapy.